Improving Community Relations: How Police Strategies to Improve Accountability for Social Equity Affect Citizen Perceptions. (4th July 2018) - McCandless, Sean
Abstract : Social equity research increasingly focuses on how accountability for social equity is achieved, or how public administrators improve the access, outcomes, processes, and quality of public services. This is particularly important to examine in police departments, which are more frequently using strategies such as community policing programs (CPPs), social equity performance measurement (SEPM), and ethics training to yield better community relations. This article explores how these strategies affect citizen perceptions through testing three propositions related to CPPs, SEPM, and ethics training. Findings are reported from interviews with 72 citizens, local-level elected leaders, and police officers from 12 purposively selected locales in the United States. Findings reveal that when CPPs foster more citizen involvement as decision-makers, SEPM is used to shape practice, and more ethics training is required, citizen perceptions of how socially equitable departments are increase. Further, as political leaders and departments more actively incorporate community groups, perceptions of social equity are more positive. These findings are discussed in terms of what they reveal about accountability for social equity.